Effects of second-generation antipsychotics on human subcutaneous adipose tissue metabolism. (December 2019) - Sarsenbayeva, Assel; Marques-Santos, Cátia M.; Thombare, Ketan; Di Nunzio, Giada; Almby, Kristina E.; Lundqvist, Martin; Eriksson, Jan W.; Pereira, Maria J.
Highlights: Therapeutic concentrations of SGAs have a mild direct effect on adipose tissue metabolism. Olanzapine dose-dependently reduces lipolysis manner in isolated adipocytes. Aripiprazole reduces glucose uptake in isolated adipocytes and adipose tissue. Both SGAs reduced expression of genes regulating mitochondrial function in adipose tissue. Both SGAs at higher concentrations acted as anti-inflammatory agents. Abstract: Objective: Metabolic syndrome is prevalent in up to 50% of schizophrenia patients, which reduces their quality of life and their compliance with the treatment. It is unclear whether metabolic adverse effects of these agents are due to their direct effect on insulin-sensitive tissues or are secondary to increased adiposity. The study aimed to investigate the direct effects of the second-generation antipsychotics olanzapine and aripiprazole on human subcutaneous adipose tissue and isolated adipocyte metabolism. Methods: Abdominal subcutaneous adipose tissue needle biopsies were taken from 72 healthy subjects (49 F/23 M; age: 19–78 yr; BMI: 20.0–35.6 kg/m 2 ). Isolated adipocytes or adipose tissue were respectively pre-incubated short- (30 min) and long-term (24 h, 72 h) with or without olanzapine (0.004 μM – 20 μM) and aripiprazole (0.002 μM – 100 μM). Pre-incubated adipose tissue was then snap-frozen for mRNA expression analysis of adipokines genes and genes involved in inflammation, adipogenesis, and mitochondrial function. Isolated adipocytes were used to measure basal and insulin-stimulated glucose uptake and lipolysis. Results: Acute treatment with a therapeutic concentration of olanzapine decreases basal lipolysis in isolated adipocytes; this effect was not observed after long-term incubation with the drug. Supra-therapeutic concentration of aripiprazole reduced basal and insulin-stimulated glucose uptake after short- and long-term pre-incubation. Both drugs at supra-therapeutic concentrations downregulated the expression of the pro-inflammatory cytokines IL6 and IL1B genes after 72 h incubation. Similarly, supra-therapeutic concentrations of both drugs and therapeutic concentration of olanzapine, reduced the expression of PPARGC1A, PDK4, and CPT1B genes involved in the regulation of mitochondrial functions. Neither of the antipsychotics affected the expression of the main adipokines LEP and ADIPOQ, genes involved in the regulation of lipid metabolism, LPL and FASN, nor the master adipogenesis regulator, PPARG . Conclusion: Therapheutic concentrations of olanzapine and aripiprazole have a moderate direct effect on adipocyte lipid and glucose metabolism, respectively. At supra-therapeutic concentrations, both of the antipsychotics seem to act as anti-inflammatory agents and mildly suppressed genes involved in the regulation of mitochondrial functions, which could potentially contribute to metabolic adverse effects. Alternatively, second-generation antipsychotics could induce metabolic side effects via acting on other insulin-sensitive tissues and central nervous system.